SUPERMARKET JAKO PRZESTRZEŃ ZNACZENIOWA. PRÓBA REKONSTRUKCJI PRZEKAZU IDEOLOGICZNEGO - Krajewski, Marek (Wydział Prawa i Administracji UAM, 1998)
The article attempts to apply such a perspective o f viewing a life of a society the central point of which is an assumption on double status of most phenomenons taking place in it. On the one hand the phenomenons are instrumental ways enabling effective activity of individuals and groups and, on the other - they are compound systems of symbols and in the same time - media of transmitting ideologies and knowledge of proper modes of action what does legitimise certam types o f organisation of a society. An example o f using such a perspective is the analysis of a supermarket (done in the article) which here is considered first o f all as specific semantic field. Withm Polish context a supermarket is above all a symbol of social change operated during several last years; it is too a projection of ideal target points of this change and, by the same, it assumes a role of an instrument of socialisation which is supposed to inculcate in the individuals some new rules of game within reality. Organisation itself o f a supermarket, a way of displaying and exponing wares, its location within the urban area, some favourite types o f behaviour of visitors-buyers - all this does prove that in contemporary Poland a consumption became central kind of activity, and further - that many from hitherto existing distinctive features of individuals or groups have definitely lost their significance and are now replaced with new distinctions and inegalities; this all proves as well that the price paid for increased effectiveness of human activity and of its rationalisation is finally also an increase o f control over all of us. A supermarket seems also to suggest that ancient systems of values have already lost their regulative power and are nowadays replaced with new secular religion - doing shopping and consumption. The analysed semantic space is additionally such a context in which satisfying of instrumental needs is synonymous with putting new normative obligations on the individuals, obligations which play a role of an authorisation for these types of social organisations that have become the effect of transformation of the society. So, a supermarket not only permits to effectively satisfy needs but is also modelling them, it designates new aspirations and creates such a vision of the world which is becoming the only one authorised or qualified interpretation of our contemporary reality.
SUPERMARKET AS SEMANTIC FIELD